Nonlinear homotopy in geodesy - Paláncz, B.; Awange, Joseph (Springer, 2017)
In Paláncz et al. (J Geod 84: 79–85, 2009), linear homotopy was introduced and its applications to geodesy presented. Never before had the concept of nonlinear homotopy been used by the geodetic community. This is partly attributed to the complexity of the involved equations and partly due to the computational time required. Recently, however, Nor et al. (MATEMATIKA 29: 159–171, 2013) suggested the possibility of constructing nonlinear homotopy. In this short note, Nor et al. (MATEMATIKA 29: 159–171, 2013) idea is developed for geodetic applications and an example of its use illustrated.